Query translation technique in cross-lingual information retrieval aproach for intellectual property documents / Muhamad Safwan Dermawan - Dermawan, Muhamad Safwan (2013)
Nowadays, information in documents can be obtained faster than before. People around the world can obtain information across countries and languages. Thus, search engines such as Google and Bing exist to provide search tools to find documents across the world. These are the examples of information retrieval (IR). IR is the act of finding information in a collection of documents. Cross-lingual information retrieval (CLIR) is much the same as general IR but it involves more than one languages. To find information in a large collection of documents is harder than it looks especially when it involves two or more languages. Translating a collection of documents from one language to another can simplify the process of searching itself but it requires a lot of efforts and time. Query translation is a good technique which can reduce the time used for this project. Query translation is a process of translating user query's language to the documents' language and target output. In this project, search engine prototype that will be produced by using query translation technique will produces relevant list of relevant documents according to user query. In conclusion, this project for searching IP documents by using query translation techniques for CLIR approach is to improve and enhance searching and retrieving of IP documents which involves two languages for students and lecturers in the field of intellectual property and other interested parties.